2013
DOI: 10.5194/isprsarchives-xl-5-w2-165-2013
|View full text |Cite
|
Sign up to set email alerts
|

3d Architectural Videomapping

Abstract: ABSTRACT:3D architectural mapping is a video projection technique that can be done with a survey of a chosen building in order to realize a perfect correspondence between its shapes and the images in projection. As a performative kind of audiovisual artifact, the real event of the 3D mapping is a combination of a registered video animation file with a real architecture. This new kind of visual art is becoming very popular and its big audience success testifies new expressive chances in the field of urban desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 5 publications
0
2
0
1
Order By: Relevance
“…The advantages of the technology used in the Padang State University ballet education department are: application in the use of video mapping or often referred to as mapping art which is applied to student dance works to support the atmosphere or setting of a performance to make it look more real and easily understood by the audience. Catanese revealed that video mapping is a method of lighting or light projection until the conclusion produces an optical illusion of the object [12]. As for the use of virtual reality is also used by the works of alumni education sendratasik.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of the technology used in the Padang State University ballet education department are: application in the use of video mapping or often referred to as mapping art which is applied to student dance works to support the atmosphere or setting of a performance to make it look more real and easily understood by the audience. Catanese revealed that video mapping is a method of lighting or light projection until the conclusion produces an optical illusion of the object [12]. As for the use of virtual reality is also used by the works of alumni education sendratasik.…”
Section: Discussionmentioning
confidence: 99%
“…Substitution generally uses a certain media or object in the form of certain animations or graphics. Likewise, as stated by Catanese that video mapping is a method of lighting or light projection until the conclusion produces an optical illusion of the object [12]. The substitution generally uses a medium or object, as well as a field.…”
Section: Introductionmentioning
confidence: 99%
“…"Haritalama" ismi bu yüzden kullanılmaktadır. " Video Haritalama: Bina ile yüzeyleri, karmaşık sistemli yüzeyler veya üç boyutlu herhangi bir objeyi yansıtma aracılığıyla, dijital teknolojilerin sunmakta olduğu yaratıcı olanakları kullanarak yüzeyleri bireyin her duyusunu zincirleme olarak aktif edecek şekilde hareketli gösterim alanına çevirmektedir" (Catanese, 2013).…”
Section: Sergġleme Mekâninda Vġdeo Harġtalama Teknġğġ Uygulamasiunclassified